Revised inventory of Chinese Ceratocanthinae (Coleoptera: Hybosoridae), emphasizing species from southeastern Xizang with description of a new species of Eusphaeropeltis Gestro - Wang, Cheng-Bin (Zootaxa, 2026)
A revised inventory of the 12 species of the subfamily Ceratocanthinae (Coleoptera: Hybosoridae) recorded thus far from China is presented, with four genera: Cyphopisthes Gestro, 1898 (2 spp.), Eusphaeropeltis Gestro, 1898 (2 spp.), Madrasostes Paulian, 1975 (5 spp.), and Pterorthochaetes Gestro, 1898 (3 spp.). Madrasostes feae (Gestro, 1898) and Pterorthochaetes dembickyi Ballerio, 2014 are newly included for China; an additional locality is reported for P. dembickyi; Eusphaeropeltis medogensis sp. nov. is described from Mêdog County. Photographic documentation of habitus and genitalia is provided for the focal taxa.